THE EFFECT OF PROBIOTICS Saccharomyces spp Gb-7 AND Gb-9 GIVEN INTO RATION TO THE PHYSICAL QUALITY OF EGG LOHMANN BROWN OF CHICKENS AT 40 TO 48 WEEKS - I G., Astawa; Bidura, I G. N. G.; Wibawa, A. A. P. P. (Jurnal Peternakan Tropika, 2018)
Egg in one of the food contains high nutrition. Egg quality is very important duc to its content. One of the efforts to increase egg quality is improving ration given to the chicken, such as probiotic supplementation. This research purpose was to find out the effect of  probiotics S accharomyces spp. Gb-7 and Gb-9 given into ration to the physical quality of egg Lohmann Brown chicken the age of 40 to 48 weeks.  This research was carried out for 12 weeks in Dajan Peken, Tabanan, Bali. The randomized complete design (RAL) with three treatments and six replicates were used in a the research. Those treatments were ration without supplementation of Saccharomyces spp. (A), ration with supplementation of 0,3% Saccharomyces spp . Gb-7 (B), and ration with supplementation 0,3% Saccharomyces spp. Gb-9 (C). The variables observed were the egg weight, white egg weight, egg yolk weight, and egg shell weight. The study result showed that ration with supplementation of 0,3% Saccharomyces spp . Gb-7 (B) and ration with supplementation 0,3% Saccharomyces spp. Gb-9 (C) significantly different (P<0,05) on the weight of the egg, the weight of egg white, the weight of egg yolk, and the weight of egg shell. Based on the result above it can be concluded that the effect of 0.3 % probiotics Saccharomyces spp . Gb-7 or Gb-9 in rations Lohmann Brown chicken at the age of 40-48 weeks can increase the physical quality of the egg which weight of egg, percentage of egg yolk, percentage of egg shell, and but has decrease percentage of white egg. Keywords:   Q uality of Physical The Chicken Egg, Lohmann Brown, Probiotic, Saccharomyces Spp .